Reflections of Researchers Involved in the Evaluation of Pedagogical Technological Innovations in a University Setting - Ives, Cindy; McWhaw, Katherine; De Simone, Christina (Canadian Journal of Higher Education, 2005)
It is widely assumed that developments in information and communication technologies are fundamentally transforming and improving higher education. As a part of an ongoing evaluation of technology-supported pedagogy in one university, our three-year research project was designed, on the one hand, to determine if and how selected technologies were beneficial for learning and, on the other hand, to offer professional development for faculty members. In this paper, we reflect on our participation in a pedagogy and technology (referred to as PedTech) pilot project, describe some of the relationships that developed between ourselves as researchers and evaluators and our faculty collaborators, and share what we have learned from this experience. We suggest that a scholarship of teaching approach to evaluating innovations in teaching and learning is one way to support institution-wide adoption.